2022
DOI: 10.34172/jhp.2023.14
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Boesenbergia rotunda extract on cisplatin-exposed human embryonic kidney-293 cells by inhibiting the expression of kidney injury molecule-1, neutrophil gelatinase associated-lipocalin, NF-κB, and caspases

Abstract: Introduction: Acute kidney injury (AKI) is a major problem in platinum-based chemotherapy patients. Boesenbergia rotunda can induce the generation of osteoblast cells and significantly increase pancreatic antioxidant enzyme activities; therefore, this study aimed to investigate the cytotoxicity of cisplatin on human embryonic kidney-293 (HEK-293) cells and the protective impact of the ethanol extract of B. rotunda (EEBR) against such conditions. Methods: Cytotoxicity was assessed using the CCK-8/WST-8 reagent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…24 Moreover, a recent study reported that B. rotunda could induce osteoblast cell proliferation 25 and significantly increase pancreatic antioxidant enzyme activities (glutathione, superoxide dismutase, and catalase). 26 Until recently, the nephroprotective activity of B. rotunda has been explored very limitedly, however, EEBR was confirmed for its protective effect on cisplatin-exposed human embryonic kidney-293 cells, 27 thus, this present study aims to investigate the nephroprotective mechanism of EEBR in cisplatin-induced male Sprague-Dawley rats by measuring the general diagnostic markers of nephrotoxicity (SCr and BUN) and the liver function parameters (glutamic oxaloacetic transaminase or GOT and glutamic pyruvic transaminase or GPT), the % relative weight of the kidney, malondialdehyde (MDA) level in the kidney, kidney histopathology, the expression of AKI biomarkers (KIM-1 and NGAL) and apoptotic pathway proteins (Casp3 and Casp7) in the kidney cortex of the rats were also evaluated using the reverse transcriptionpolymerase chain reaction (RT-PCR).…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, a recent study reported that B. rotunda could induce osteoblast cell proliferation 25 and significantly increase pancreatic antioxidant enzyme activities (glutathione, superoxide dismutase, and catalase). 26 Until recently, the nephroprotective activity of B. rotunda has been explored very limitedly, however, EEBR was confirmed for its protective effect on cisplatin-exposed human embryonic kidney-293 cells, 27 thus, this present study aims to investigate the nephroprotective mechanism of EEBR in cisplatin-induced male Sprague-Dawley rats by measuring the general diagnostic markers of nephrotoxicity (SCr and BUN) and the liver function parameters (glutamic oxaloacetic transaminase or GOT and glutamic pyruvic transaminase or GPT), the % relative weight of the kidney, malondialdehyde (MDA) level in the kidney, kidney histopathology, the expression of AKI biomarkers (KIM-1 and NGAL) and apoptotic pathway proteins (Casp3 and Casp7) in the kidney cortex of the rats were also evaluated using the reverse transcriptionpolymerase chain reaction (RT-PCR).…”
Section: Introductionmentioning
confidence: 99%